2007
DOI: 10.1021/jp067327s
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Nitrile-Functionalized Ionic Liquids

Abstract: A series of ionic liquids (ILs) based on nitrile-functionalized imidazolium, pyridinium, and quaternary ammonium as cations and chlorides and tetrafluoroborate, hexafluorophosphate, dicyanamide, and bis(trifluoromethanesulfonyl)imide as anions have been prepared and characterized. The physicochemical properties such as spectroscopic, thermal, solubility, surface, electrochemical, tribological, and toxic properties were comparatively studied. The results showed that the incorporation of a CN group to cations co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
162
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(183 citation statements)
references
References 51 publications
16
162
5
Order By: Relevance
“…In this work, we have studied the possibility of using ionic liquids for the separation of light saturated and unsaturated hydrocarbons and have started by compiling the literature results on the solubility of ethane and ethylene in different ionic liquids formed by the cations and anions in Table 1. The Henry's law constants for ethane and ethylene are reported in Figure 2 [2,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and Table 2 ). The authors observed that small changes in the structure of the ionic liquid can have large effects in the ethane and ethylene solubility as illustrated in Figure 2 and can significantly influence the ideal selectivity of ethylene as shown in Figure 3 [9-26, 28, 29].…”
Section: Ionic Liquids As Separating Agentsmentioning
confidence: 99%
“…In this work, we have studied the possibility of using ionic liquids for the separation of light saturated and unsaturated hydrocarbons and have started by compiling the literature results on the solubility of ethane and ethylene in different ionic liquids formed by the cations and anions in Table 1. The Henry's law constants for ethane and ethylene are reported in Figure 2 [2,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and Table 2 ). The authors observed that small changes in the structure of the ionic liquid can have large effects in the ethane and ethylene solubility as illustrated in Figure 2 and can significantly influence the ideal selectivity of ethylene as shown in Figure 3 [9-26, 28, 29].…”
Section: Ionic Liquids As Separating Agentsmentioning
confidence: 99%
“…[49] Similarly to the viscosity, the structure variation in the cation and anion has some impact on the refractive indices of ILs. In general, for the same cation, the high refractive indices of the ILs reflect particularly high electron mobility in the anion.…”
Section: à3mentioning
confidence: 99%
“…Melting temperature of the eutectic is well below that of the AlCl 3 , representing the minimum liquid us temperature throughout the entire system. We continue to focus on the synthesis and characterization of various ionic liquids [12][13][14] . In this Ionic liquid was synthesized through a one-step reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, ionic liquid properties such as heat capacities and refractive index 8 , luminescence properties 9 , osmotic coefficients 10 , enthalpy, density, heat capacity 11 , and thermophysical properties 11 have been studied since their first synthesis. Therewith, following our previous studies on ionic liquids' chemistry [13][14][15] , we decided to improve our knowledge about these compounds by synthesis, characterization, and theoretical the study of a new aluminum-based ionic liquid. This is useful when a metal catalyst is used in the reaction that is this catalyst often remains in the ionic liquid and can be directly reused.…”
mentioning
confidence: 99%